PERLINDUNGAN HUKUM TERHADAP PEKERJA WAKTU TERTENTU YANG DIKENAKAN PEMUTUSAN HUBUNGAN KERJA AKIBAT PANDEMI COVID-19 - Yosephine Fransisca Andriani (2022)
The focus of this research is to analyze the legal protection for workers with a certain time work agreement that is subject to termination of employment due to the Covid-19 Pandemic. This study uses a normative juridical method with a statutory approach and a theoretical point of view from books and scientific journals. The results of the discussion in this study are the authors find differences in the rights received by workers for a certain time before and after the enactment of PP No. 35 of 2021 which is now a guide to the employment relationship between employers and workers for a certain time. In addition, this study also found what are the legal protections for workers for a certain period of time. This serves to provide a sense of security and justice for workers at a certain time. In addition, in terms of resolving disputes over termination of employment, there are several procedures that must be carried out, where this is written in Law no. 2 of 2004. The state continues to seek ways to reduce the number of layoffs with various policies. With the issuance of these various policies, it is hoped that employers can consider decisions in unilaterally terminating workers. This study also discusses the rights that should be obtained by Certain Time Workers who are subject to termination of employment before the contract period ends, so that it is expected to provide benefits for readers. Keywords: Legal Protection, Fixed Time Employment Agreement, Termination of Employment